Risk factors for cardiovascular disease in professors from a public university - Costa Moreira, Osvaldo; Rodrigues de Oliveira, Renata Aparecida; Patrocínio Oliveira, Cláudia Eliza; Doimo, Leonice Aparecida; dos Santos Amorim, Paulo Roberto; Camaroti Laterza, Mateus; Monteiro, Walace David; Bouzas Marins, João Carlos (Investigación y Educación en Enfermería, 2014)
Objective. To determine the prevalence of risk factors for cardiovascular disease among professors of a public university. Method. This cross-sectional study included 145 professors from the Federal University of Viçosa (UFV), MG, Brazil, in 2010. Analyzed variables included age, weight, height, waist, hip and abdominal circumferences, in addition to total cholesterol, triglycerides, glucose, and resting systolic and diastolic blood pressures. Results. A total of 71% were men, the average age of the men was higher than that of the women (46.9 versus 43.2 years old); half of the participants were overweight (46.9% were overweight and 9.0% were obese). Other factors were: 17.2% presented a waist-hip ratio at risk; 46.9% had greater than normal abdominal circumference; 4.0% presented high total cholesterol, 20.2% high triglycerides, 4.8% of the individuals presented abnormal glucose metabolism; and 16.6% were hypertensive. In comparison with men, women presented lower systolic blood pressure, diastolic blood pressure, body mass index, and abdominal, hip and waist circumferences. There was a trend of increased waist/hip and abdominal circumferences, total cholesterol, triglycerides, and systolic blood pressure as individuals aged. Conclusion. The college professors addressed in this study present important risk factors for cardiovascular disease. Hence, prevention and control measures need to be implemented in order to reduce the problem, a process in which nursing professionals play a key role in the achievement of success.